Personal growth experiences of young adults recovering from major depressive disorder / Chan Siaw Leng - Chan , Siaw Leng (2018)
Major depression is one the most severe form of depressive disorder. In Malaysia, a remarkably increasing trend of the prevalence of depression among young adults was indeed an alarming phenomenon in the country and it necessitates responsiveness and act. The objective of this study was to investigate and describe the subjective personal growth experience of young adults recovering from major depressive disorder (MDD), taking an in-depth look at the essence of their personal growth journey during recovery based on their own perspectives. A qualitative, transcendental phenomenological research design was adopted by using in-depth, semi-structured, phenomenological three-interview series to collect data, supported with audio recordings, interview transcripts, and documents. A fitting sample of nine Malaysian young adults (one man and eight women) with MDD, ranging from 20-39 years (Mean age=28), were recruited from tertiary healthcare setting in Perak and Kuala Lumpur, Malaysia. Pseudonyms were used in a total of 27 in-depth interview sessions were carried out with each session ranging from 45 to 90 minutes. The method of data analysis was based on Colaizzi‟s phenomenology data analysis. The findings focused on the narrative sharing from young adults recovering from MDD, indicated by evidence in participants‟ statements. Research findings revealed a total of fourteen personal growth themes: (a) Revealing the struggles, (b) Self-discovery and personal strength, (c) Personal responsibility, (d) Readiness for change, (e), Hope, (f) Redefining the meaning, (g) Forgiveness, (h) Acceptance, (i) Supportive relationship, (j) Medication, (k) Attending counselling, (l) Religion and spirituality, (m) Care for others, and (n) Employment, which have facilitated the participants to recover from MDD. All emerging themes were separated into two main elements: personal growth processes (eight themes) and personal growth contributors (six themes). In conclusion, all themes in both elements were interconnected throughout the recovering journey of major depressive young adults. Hence, practitioners and researchers need to be more objective and conscientious of both elements to understand their prospective clients‟ personal growth experiences. The ability in identifying every aspect in personal growth processes and contributors will give extra credits for practitioners or researchers to embrace a holistic view of the personal growth experiences faced by young adults upon helping them to reach recovery stage. The crucial implications of this study for counselling and psychotherapy practice, education and training; psychotherapy models on personal growth and healing from MDD; future research; and policy development were discussed. It is recommended in the future to have more researchers conduct more qualitative studies as it will help contribute to deeper understanding about personal growth experiences recovering from MDD, particularly based on the young adults‟ perspective.